Privatization of prisons: solution to prison congestion in Nigeria? (2012)
The aim of establishing the prison Institution in all parts of the world including Nigeria is to produce a rehabilitation and correctional facility for people who have violated the rules and regulations of their society. The extent to which this is true in practice has been a subject of discussion. An observation of the population that goes in and out of the prisons in Nigeria shows that there are problems in the System, hence, over time, the prison System has not been able to live up to its expected role in Nigeria. An enquiry into the state of prisons in Nigeria will reveal a System afflicted with over-population and a litany of human right abuses and contradictions, including incessant occurrences of jail breaks. Undoubtedly, the prisons are run at more than 150% capacity as no less than 60% of the inmates await trial. The problem of over-crowding and unhygienic conditions of Nigerian prisons has remained a source of worry and has continued to attract rapidly increasing attention among scholars and policy makers. Aware of the poor condition of Nigerian prisons, government has undertaken a number of reforms in the last decade which have no less failed to adequately address the poor state of prisons in Nigeria On the other hand, many scholars have proffered Solutions to the horrifying state of Nigerian prisons, including privatization as an alternative mechanism to address the contradiction that characterizes the prison System. This paper examines the history, objectives and modes of privatization of prisons, as well as the viability of privatizing Nigerian prisons